PENGARUH POLA ASUH TERHADAP GANGGUAN PERTUMBUHAN BAYI SAMPAI UMUR SEMBILAN BULAN: Studi Kasus di Kecamatan Sukaraja, Kabupaten Bogor - Agus Triwinarto; Anies Irawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2004)
The Effect of Child Caring Practices To Infant Growth Faltering Since Birth To 9 Months Olds: A Case Study In Sub District Sukaraja, District Bogor.Introduction: Growth faltering in Indonesian infant started when they are less than six month old and continued untill they grow up. Child care including feeding pattern may as aa caused this problem.  The main factors related with growth faltering are unbalanced food consumption (macro and micro nutrient) and infectious disease.Objectives: The study was aimed to assess the contribution of infant care to infant growth faltering before they reach age of nine month old. The study was designed as cohort prospective Fifty-nine babies were followed from birth until nine months old, in Sukaraja Subdistrict, Bogor Regency. Child care aspects being monitored were feeding pattern, nutrition comsumption and health care. Infant growth measured by weight and length gain, based on CDC-NCHS 2000 growth curve. Repeated measured analysis were used to evaluate when growth faltering begins. Multiple linier regressions were used to evaluate the impact of child care on infant growth.Result: The result of the study showed that child care significantly contribute infant weight gain and lenght gain when birth weight, birth length, frequency of infection, sex, age of mother, education of mother, nutrition and health knowledge of mother and ratio food to total expenditure were controlled. Growth faltering in weight due to child care starts when they reach two mothers old, and continue until nine months old. Growth faltering in length due to child care starts when they reach five months old, and continue until they the age reach nine months.Conclusions: Infant care especially during the first month of life is an important period to prevent infant from early growth faltering.Keywords: child care, feeding pattern, growth faltering